2018
DOI: 10.3171/2018.5.peds182
|View full text |Cite
|
Sign up to set email alerts
|

Secondary overtriage of pediatric neurosurgical trauma at a Level I pediatric trauma center

Abstract: OBJECTIVEThe authors reviewed the transfer requests for isolated pediatric traumatic brain injuries (TBIs) at a Level I/II facility with the goal of identifying clinical and radiographic traits associated with potentially avoidable transfers that could be safely managed in a non–tertiary care setting.METHODSThe authors conducted a retrospective study of patients < 18 years of age classified as having TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Our data answers a specific question that previous papers have alluded to, but not emphasized, in their results [6, 7, 10, 12, 14, 15]. To briefly summarize, Arrey et al [6] determined that there was no need to hospitalize 326 patients with ILSF with a median age of 19 months unless there was a pending nonaccidental trauma workup.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Our data answers a specific question that previous papers have alluded to, but not emphasized, in their results [6, 7, 10, 12, 14, 15]. To briefly summarize, Arrey et al [6] determined that there was no need to hospitalize 326 patients with ILSF with a median age of 19 months unless there was a pending nonaccidental trauma workup.…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, Tavor et al [17] retrospectively demonstrated that severe mechanism of injury (running, biking, fall onto protruding instrument) combined with clinically evident skull fracture, neurological deficit, and severe headache identified almost all 182 patients who required intervention in their study. Similarly, Mackel et al [12] found that an intracranial finding or altered mental status may be predictive for future intervention. These studies taken together suggest that the typical fracture requiring neurosurgical intervention results from a severe mechanism of injury, is associated with some symptoms at the time of presentation, has additional intracranial pathology, and typically involves the frontal or temporal bone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations